Oxime-phosphazenes containing dioxybiphenyl groups - Cil, Erol; Arslan, Mustafa (Elsevier Science Sa, 2009)
2,2-Dichloro-4,4,6,6-bis[spiro(2',2 ''-dioxy-1',1 ''-biphenylyl]cyclotriphosphazene (2) was obtained from the reaction of hexachlorocyclotriphosphazene (1) with biphenyl-2,2'-diol. 2,2-Bis(4-formylphenoxy)-4,4,6,6-bis[ spiro(2',2 ''-dioxy-1',1 ''-biphenylyl] cyclotriphosphazene (3) was synthesized from the reaction of 2 with 4-hydroxybenzaldehyde. The novel oxime-cyclophosphazene containing dioxybiphenyl groups (4) was synthesized from the reaction of 3 with hydroxylaminehydrochloride in pyridine. The reactions of this oxime-cyclophosphazene with propanoyl chloride, allyl bromide, acetyl chloride, methyl iodide, benzoyl chloride, 4-methoxybenzoyl chloride, benzenesulfonyl chloride, chloroacetyl chloride, ethyl bromide, benzyl chloride and 2-chlorobenzoyl chloride were studied. Disubstituted compounds were obtained from the reactions of 4 with propanoyl chloride, allyl bromide, acetyl chloride, methyl iodide, benzoyl chloride, 4-methoxybenzoyl chloride, chloroacetyl chloride, ethyl bromide, and 2-chlorobenzoyl chloride, however, the oxime groups on 4 rearranged to nitrile (11) in the reaction of 4 with benzenesulfonyl chloride. A monosubstituted compound was obtained from the reaction of 4 with benzyl chloride. All products were generally obtained in high yields. The structures of the compounds were defined by elemental analysis, IR, (1)H, (13)C and (31)P NMR spectroscopy. (C) 2008 Elsevier B. V. All rights reserved.
Keywords: Hexachlorocyclotriphosphazene; Phosphazene; Oxime; Oxime derivatives; Oxime-phosphazenes